DECISION ANALYSIS OF SELECTING POSTGRADUATE PROGRAMS THROUGH PLACE, MARKETING COMMUNICATION, PRICE PERCEPTION AND SERVICE QUALITY (SURVEY OF ENGINEERING FACULTY STUDENTS AT WEST JAKARTA REGIONAL UNIVERSITY) - Zulfi Assakhir, Rezza; Permana, Dudi (Dinasti Publisher, 2021)
This study aims to analyze the decision analysis to choose a postgraduate program through Place, Marketing Communication, Price Perception and Service Quality. The results of the study using primary data in the form of questionnaires to 100 students of the Faculty of Engineering at the University of West Jakarta with the Structural Equation Modeling (SEM) method showed that Place, Marketing Communication, Price Perception and Service Quality had a positive and significant effect on the decision to choose a postgraduate program. Judging from the results of the SEM Place calculation analysis has an estimate coefficient of 0.36 or 36%, Marketing Communication has an estimate coefficient of 0.15 or 15%, Price Perception has an estimate coefficient of 0.30 or 30%, Service Quality has an estimate coefficient of 0.24 or 24% influence on the decision to choose a postgraduate program. This shows that if Place, Marketing Communication, Price Perception and Service Quality have increased, it will affect the decision to choose a Postgraduate Program